Development of a Child-Friendly School Training Center (CFSTC) Model to Improve Teachers’ Ability to Handle Aggressive Behavior of Kindergarten Children: A Quasi-Experimental Study - Yafie, Evania; Atmoko, Adi; Tirtaningsih, Munaisra Tri; Widianingsih, Rina Mukti; Azizah, Suti Mega Nur (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2025)
This study developed and evaluated a Child Friendly School Training Center (CFSTC) Model aimed at improving teachers’ skills in managing aggressive behavior in kindergarten children. Utilizing a quasi-experimental design, nine teachers at TK Kemala Bhayangkari 11 Tumpang underwent training and were assessed through pre- and post-tests. The results demonstrated significant improvements in teachers’ understanding of child-friendly practices. Scores for “Introduction to Child Friendly School” increased from 71.5 to 85 (t = 3.923; p = 0.001), “Types of Aggressive Behavior” from 68 to 79 (t = 4.134; p = 0.000), and “Causes of Aggressive Children” from 70 to 83 (t = 3.123; p = 0.025). Validity and reliability tests (r-count > 0.25; Cronbach’s alpha > 0.60) confirmed robust measurement. The CFSTC Model’s structured modules, group discussions, and simulations enhanced teachers’ ability to identify aggression and implement child-friendly interventions. These findings underscore the efficacy of targeted professional development in fostering safe, empathetic learning environments. By integrating child-friendly strategies, educators can more effectively address early aggressive behaviors and support socioemotional growth. This study provides evidence that a structured training approach can be instrumental in reducing aggression and improving the overall classroom climate in early childhood education.